2023
DOI: 10.1038/s41389-023-00474-2
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of single-cell and bulk RNA sequencing data reveals an immunostimulatory microenvironment in tumor thrombus of osteosarcoma

Abstract: Tumor thrombus of bone sarcomas represents a unique reservoir for various types of cancer and immune cells, however, the investigation of tumor thrombus at a single-cell level is very limited. And it is still an open question to identify the thrombus-specific tumor microenvironment that is associated with the tumor-adaptive immune response. Here, by analyzing bulk tissue and single-cell level transcriptome from the paired thrombus and primary tumor samples of osteosarcoma (OS) patients, we define the immunosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Pahl et al observed that M1 macrophages, activated by LPS and IFN-γ, effectively suppress osteosarcoma cell proliferation, demonstrating an advantageous role in osteosarcoma immunotherapy ( Pahl et al, 2014 ). Furthermore, Ji et al confirmed that osteosarcoma tumor thrombi contain a substantial proportion of M1-like macrophages (TAM-M1), exhibiting an immunostimulatory state, positively influencing the activation of anti-tumor immune responses ( Ji et al, 2023 ). Simultaneously, according to Gong et al, MPIRx nanoparticles prompt a specific mechanism causing macrophage polarization towards the M1 phenotype, thereby augmenting macrophage phagocytic function against osteosarcoma cells and contributing to an anti-tumor effect ( Gong et al, 2023 ).…”
Section: Immune Cellsmentioning
confidence: 99%
“…Pahl et al observed that M1 macrophages, activated by LPS and IFN-γ, effectively suppress osteosarcoma cell proliferation, demonstrating an advantageous role in osteosarcoma immunotherapy ( Pahl et al, 2014 ). Furthermore, Ji et al confirmed that osteosarcoma tumor thrombi contain a substantial proportion of M1-like macrophages (TAM-M1), exhibiting an immunostimulatory state, positively influencing the activation of anti-tumor immune responses ( Ji et al, 2023 ). Simultaneously, according to Gong et al, MPIRx nanoparticles prompt a specific mechanism causing macrophage polarization towards the M1 phenotype, thereby augmenting macrophage phagocytic function against osteosarcoma cells and contributing to an anti-tumor effect ( Gong et al, 2023 ).…”
Section: Immune Cellsmentioning
confidence: 99%
“…Preclinical research has shown that osteosarcoma cells educate these MSCs by secreting TGF-βcontaining extracellular vesicles that drive the formation of metastatic foci within the lungs [12]. Ji et al [13] also revealed that elevated IFN-γ signaling indicates the antitumor immune response in metastatic osteosarcoma thrombus by paired samples single-cell and bulk RNA sequencing data. Liu et al [14] used a comprehensive landscape of TGF-β-related signatures to predict prognosis, immune characteristics, and therapeutic response for osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%